Oncolytic reovirus enhances rituximab-mediated antibody-dependent cellular cytotoxicity against chronic lymphocytic leukaemia - Parrish, C (Leukemia, 2015)
The naturally occurring oncolytic virus (OV), reovirus, replicates in cancer cells causing direct cytotoxicity, and can activate innate and adaptive immune responses to facilitate tumour clearance. Reovirus is safe, well tolerated and currently in clinical testing for the treatment of multiple myeloma, in combination with dexamethasone/carfilzomib. Activation of natural killer (NK) cells has been observed after systemic delivery of reovirus to cancer patients; however, the ability of OV to potentiate NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC) is unexplored. This study elucidates the potential of oncolytic reovirus for the treatment of chronic lymphocytic leukaemia (CLL), both as a direct cytotoxic agent and as an immunomodulator. We demonstrate that reovirus: (i) is directly cytotoxic against CLL, which requires replication-competent virus; (ii) phenotypically and functionally activates patient NK cells via a monocyte-derived interferon-α (IFNα)-dependent mechanism; and (iii) enhances ADCC-mediated killing of CLL in combination with anti-CD20 antibodies. Our data provide strong preclinical evidence to support the use of reovirus in combination with anti-CD20 immunotherapy for the treatment of CLL.